Relative Salary Efficiency of PGA Tour Golfers: A Dynamic Review. (2011)
Based on one-year sample, Nero (2001) estimated golfers' earnings using four performance measures. We study the effects of the golfers’ abilities and skills on their earnings by estimating a production function for four different years (1995, 2000, 2005 and 2009). Our findings suggest that the effect of each skill and ability changes over time. In this sense, our results show that previous work as Nero (2001) cannot be extrapolated to other years. We also show that a dynamic approach is needed to understand the nature of professional golfers' job performance